PERAN DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN SLEMAN DALAM MENDUKUNG DIGITALISASI ADMINISTRASI DI LINGKUNGAN PEMERINTAH KABUPATEN SLEMAN - Nafiah, Daimatun (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This study aims to describe the role of the Department of Communication and Informatics of Sleman Regency in supporting administrative digitalization within the Sleman Regency Government. The research design used is descriptive qualitative research with a case study approach. Data collection techniques include observation, interviews, and documentation studies.The results of this study conclude that: 1). The Department of Communication and Informatics of Sleman Regency plays an important role in supporting administrative digitalization within the Sleman Regency Government through the provision of information technology infrastructure, the development of electronic office applications, and training to enhance the competence of government personnel. In addition, the Department also ensures data and network security and promotes the implementation of an Electronic-Based Government System (SPBE), making administrative processes more efficient, transparent, and accountable. 2). Several systems and applications are utilized to support administrative digitalization, including E-Office (correspondence), Lapor Sleman (a local innovation application), SP4N Lapor,SINP (Attendance Information System), Regional Asset Inventory Information System, SIPD (Regional Government Information System), the official Sleman Regency Government Website, SMS Gateway, various social media platforms, and Padukuhan Wi-Fi networks. 3). Some obstacles in improving the effectiveness of administrative digitalization include limited human resources, technical challenges such as system disruptions or suboptimal integration between applications, uneven technological infrastructure particularly in remote areas with limited network access and insufficient adaptation to a digital work culture. 4). To overcome these challenges, several efforts have been made, including capacity building for human resources, providing direct technical assistance to government offices (OPD) facing difficulties in using digital applications, improving application systems to make them more stable and integrated through the SPBE portal, developing network infrastructure in underserved areas, and fostering a digital work culture that is adaptive and open to change.